ENHANCING ORGANIZATION PERFORMANCE THROUGH THE IMPLEMENTATION OF MS1900:2005 - Rehat, Afiq; Hamid, Syaiful; Ridzuan, Mohamad Nazmi; Boon Cheong, Chew (Journal of Technology Management and Business, 2016)
MS 1900 is a holistic Islamic quality management system that incorporates its principles and requirements. The research utilized five requirements on MS1900:2005 that can enhance the organization performance advocated by Malik (2009). The system does not only help organization to improve their management system, but also enables organization to practice management system that complies with Shariah and Islamic obligations. Complying Shariah obligations will lead to many benefits to organizations such as market growth, increasing public trust, increasing confidence of Muslim customers, enhancing Islamic quality culture and improving organization management at large. To explore all the factors, the researcher uses the survey method which consists of 35 quantitative questionnaires that relate to the research objective and also the research questions. The quantitative questionnaires have been distributed among the organizations that have been certified with MS 1900:2005. As a conclusion, MS1900:2005 have being the standard that based on Islamic guidelines on work quality by becoming the yardstick to evaluate the efficiency of activities held by the particular organisation according to quality management systems, management responsibility, resources management, product realization and lastly, measurement, analysis and improvement.